Marketing Communication Implementation of Periplus and Kinokuniya during Pandemic in Indonesia - Putri, Annisa Dwida Sunggowo (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2024)
The retail sector in Indonesia, including book retailers, faced considerable challenges due to the COVID-19 pandemic. Despite the country's high literacy index, the reading culture's lack of alignment created ongoing obstacles for bookstores and hindered book sales growth. This research's goal is to comprehend the vital role of marketing communication in assisting companies in navigating unpredictable events like the pandemic. Employing qualitative research and grounded theory, the study collected data through interviews with two customers each from Periplus and Kinokuniya, who bought books between 2020 and 2021. The investigation compares the marketing strategies of both companies during the pandemic, highlighting essential elements. Kinokuniya effectively facilitated purchasing choices by emphasizing DRIP components (differentiation, reinforcement, information, persuasion), while Periplus concentrated on informing and differentiation via notable discount campaigns. However, Periplus could enhance its persuasive aspect. These findings offer insights for refining marketing strategies for uncertain periods for book retailers.